2017
DOI: 10.17576/jsm-2017-4609-37
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of the Present Stability and Performance of EOR-Foam

Abstract: Foam flooding technique, commonly known as foam assisted water alternating gas method (FAWAG)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…One of the methods in enhanced oil recovery, EOR is surfactant flooding method employed to recover part of the residual oil left behind by water flooding. Surfactant flooding has been around for more than four decades and several reviews have been reported with the recent ones on surfactant flooding 1 , foam assisted 2 and nanotechnology for EOR 3 . Surfactants are special compounds that combine hydrophobic and hydrophilic molecules that constitute stable configuration in water and crude oil interfaces.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the methods in enhanced oil recovery, EOR is surfactant flooding method employed to recover part of the residual oil left behind by water flooding. Surfactant flooding has been around for more than four decades and several reviews have been reported with the recent ones on surfactant flooding 1 , foam assisted 2 and nanotechnology for EOR 3 . Surfactants are special compounds that combine hydrophobic and hydrophilic molecules that constitute stable configuration in water and crude oil interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…The use of surfactant in the oil recovery is well documented [1][2][3] . However, several works reported different result by using surfactant and polymer.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the oil resistance of the foam is evaluated via recording its volume decay under the impact of crude oil (Figure ). The crude oil can easily enter the foam film, resulting in the fabrication of the hydrophobic bridge among neighboring foam bubbles and high disjoint pressure, which directly leads to the rapid rupture of foam bubbles. Then, the PMIE-stabilized foam almost completely disappears at 30 min, whereas the PMIE–JS n -stabilized foam, especially the PMIE–JS3 system, displays remarkable oil resistance with the remaining relative foam volume of about 35% at even 500 min, which should be attributed to the highly improved intensity of the foam film by the irreversibly adsorbed JS3 NPs.…”
Section: Resultsmentioning
confidence: 99%